Commodity murabahah as an underlying concept for demand deposit structure - Suhaib bin Torla (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Malaysia is the leading Islamic finance hub, but has a dual-banking system that needs to be addressed by Islamic financial institutions (IFIs). And although IFIs in Malaysia have been resilient and competitive against its conventional counterpart, the enactment of the Islamic Financial Services Act 2013 (the Act) has made a huge short-term impact on IFIs, particularly with respect to its liquidity and liability management. The case is due to the restrictions imposed by Wadīʻah and Qarḍ-based deposits, where promising returns or any kind of benefit will tantamount to ribā which is prohibited in Islam. This has made IFIs in Malaysia unable to compete with the conventional counterparts, in terms of attracting low cost funds. As the method of attracting low cost funding is vital for IFIs to remain competitive in Malaysia's dual-banking system, this research attempts to structure a demand deposit product based on Commodity Murābaḥah which will enable IFIs to command back the market share of deposits.